Migracje wewnętrzne w Niemczech i ich determinanty: - - Pastuszka, Sławomir; Szczepaniak, Daniela (Studia prawno-ekonomiczne, 2019)
Background: The subject of the study is the analysis of internal migration in Germany. Research purpose: The paper aims to indicate the size and direction of migration flows between the Länder of Germany in the years 2005–2016 and to assess the degree of dependence between these migration flows and economic determinants. Methods: In the analysis, we used descriptive methods of migration flows, differentiation analysis, wages, and unemployment rates in time and space. We also used spatial econometrics methods: the least squares method (LSM), generalized method of moments (GMM), logistic models, and fixed effects models. Conclusions: The results of the research show that beneficiaries of the net migration flows were six German Länder, including four western Länder: Bayern, Baden-Württemberg, Hamburg, Schleswig-Holstein, and two eastern Länder: Berlin and Brandenburg. It was also proved that the geographical distance and travel time had the greatest impact on migration flows, followed by the possibility of finding a job.